Evaluasi Penggunaan Website Kampus Menggunakan Metode Usability Testing dan System Usability Scale - Inna Ekawati; Malikus Sumadyo; Retno Nugroho Whidhiasih (JREC (Journal of Electrical and Electronics), 2023)
The campus website is the face of an institution that can be accessed online by everyone because the website is a central information service. When individuals such as potential students, the wider public, and those within the institution itself require information about the campus, they will primarily turn to the website as their main source. However, not all campus websites have a perfect role as information and service centers. The quality of a campus website can be seen from the perception and feedback of its users. Therefore, an assessment of online media usage, especially websites, is essential at all times to understand user perceptions of the ongoing website development. This research is intended to evaluate the usability of the website of Islamic University 45 Bekasi to obtain the best recommendations for improvement. In addition to the evaluation, this research also compares two methods of website usability evaluation. The methods to be used are usability testing and the System Usability Scale. Both methods are conducted simultaneously to obtain qualitative and quantitative data. This research yields recommendations for areas that need improvement or enhancement and also provides a comparison of the two methods used as references for usability evaluation. The research results reveal that with the first method, there is a significantly higher number of positive perceptions than negative ones, although there are many suggestions for improvement. On the other hand, when using the second method, the campus website exhibits the second least favorable usability score among a total of eleven levels.